Faktor-Faktor yang Memengaruhi Perkembangan Industri Kreatif pada 10 Kota di Indonesia - Alfath Prannisa (Epistemik: Indonesian Journal of Social and Political Science, 2020)
Creative industries can be interpreted as economic activities related to innovation, creativity, ideas and ideas originating or relying on human resources (human activities), so that their products, both goods and services, have greater added value. According to the Indonesian Creative Economy Agency, there are 16 creative industry sub-sectors and 10 creative cities. This study analyzes the factors that influence the added value of the creative industry in the classification of creative cities in Indonesia in 2005-2015. This study uses quantitative analysis with a secondary data approach to the classification of creative cities in Indonesia according to the Creative Economy Agency, namely Jakarta, Bali, Surabaya, Bandung, Padang, Yogyakarta, Malang, Pekalongan, Surakarta and Banyuwangi. The data obtained were analyzed using classical assumption test and statistical test. The data analysis technique used is panel data regression analysis because it is a combination of cross section and time series data. The results of the analysis show that the development of the creative industry in Indonesia fluctuates. The development of value added, capital and labor has mixed results. Statistical results show that the labor variable has a significant effect on the added value of the creative industry at the national level either simultaneously or partially, while the capital variable does not significantly affect the added value partially. At the city-district or provincial level, the results vary partially, in some areas there are variables of capital and labor that have a significant effect on added value, either partially or simultaneously. While in other areas the capital variable does not have a significant effect on added value partially.